Hearts, not heads in university. Student's feelings towards evaluation - Miguel Ángel Santos Guerra (Universitat Politècnica de València, 2015)
The  role  of  feelings  in  the  learning processes of university students is stated in the article first. Later some reflections on the process of assessing students are made, distinguishing it from other types of evaluation and noting some pitfalls of language. Below are the implications of the evaluation, especially in the emotional life of the students are analyzed. Influence on the self-concept, self-fulfilling prophecies, impact  of  coldness  ordeal  of  claims and evaluation as torture: five cases of student assessment and side effects in the  emotional  sphere  arise.  Then  the need to assess the heart shown, because the assessment is a technical process but, above all, is a psychological and ethical process. Section with some comments on understanding and improving assessment practices at the University is closed. You are  invited  to  discuss,  participate  and negotiate  assessments  and  practical rationality model is proposed as a basic strategy improvement. Throughout  the  text  reveals  how  they act and how they react college students today, meaning that rather than actors, are recipients of the decisions of politicians and teachers are those who plan the curriculum, those who develop and evaluated. Text for students claiming a greater role as the axis of responsibility, learning and motivation is closed.